Enabling Teaching and Learning Environments in a Contact-Less World - Idoga, Patience E; Kazaure, Ahamed Sani (Asian Journal of Contemporary Education, 2022)
The educational paradigm is constantly evolving; this is largely due to continuous emerging educational tools and technologies. This development has altered the traditional ways of teaching and learning. Present global trends have further increased or forced the adoption of technology in all its ramifications, resulting in a reliance that could have prolonged implications for teaching and learning activities and outcomes. This study discusses the need for enabling teaching and learning environments in the face of swift and continuing technological developments in a post global pandemic era, which has resulted in a contactless world. Metadata and abstracts of reviews on studies were retrieved from science direct database via the search words “enhanced teaching/learning” and “teaching/learning in COVID-19 era”, published between the years 2018 - 2020 and the years 2020–2021 for teaching and learning in a COVID-19 era. This search led to the retrieval of articles on enhanced teaching and learning activities and subsequently articles related to the COVID-19 era. The findings from this study reveal that strategic planning of teaching and learning processes have to be reevaluated.